Type Of Breast Pump And The Affect To Pain Scale, Milk Production, And Pumping Time In Breastfeeding Mothers - Susilo Rini; Suryo Ediyono; Wilis Sukmaningtyas; Arlyana Hikmanti; Ikhwan Yuda Kusuma (Poltekkes Kemenkes Surakarta, 2022)
Background: As we know that breastfeeding saves children under five lives every year, especially during the Covid-19 pandemic. The facts show that only 43% of infants 0-6 months are exclusively breastfed. The limited time for breast milk expression in between the mother's work routine needs to be supported by an efficient and effective pump. This study aimed to assess the type of breast pump not affect to pain scale, milk production, and pumping time in breastfeeding mothers. Methods: This research is a cross-sectional study with a sample of 36 breastfeeding mothers in Banyumas Regency. They were chosen by distributing survey invitations through the WhatsApp group with a background breastfeeding mothers. Data was collected using the Google form, and analyzed using the Chi Square statistical test with a significance level of 95% (Alpha 0.05). Results: Chi-Square analysis test shows the Asymp value. Sig. (2-sided) for the relationship between the type of Breast Pump and the Pain Scale, the volume of breast milk expressed, and the duration of pumping are 0.001; 0.905; 0.620, so only pain scale which less than α >0,05, the others are more than α >0,05. This result means any correlation between the type of breast pump with pain scale but no correlation with the amount of milk expressed, and the time spent pumping. Conclusion: There is no relationship between the type of breast pump, the amount of milk expressed, and the time spent pumping, but any correlation between pain scale. So breastfeeding mothers can choose any breast pump that fits their needs and consider other factors influencing breastfeeding success.